ANALISIS PENGARUH NILAI TUKAR, TINGKAT SUKU BUNGA, DAN PDB TERHADAP NERACA PERDAGANGAN INDONESIA - Tasya Vannezia (2023)
The trade balance certainly has an influence in carrying out international trade carried out by each country, because every activity that occurs in international trade such as exports and imports needs to be recorded in order to see that a country's trade balance is in a surplus or deficit position. Differences in the natural resources that each region or nation owns can influence international trade. Several variables, including currency rates, interest rates, and gross domestic product, can affect Indonesia's trade balance The purpose of this study is to examine the impact of GDP, interest rates, and currency rates on Indonesia's trade balance. Indonesia served as the study's subject, and samples from 1991 to 2021 were used. The Error Correction Model is the analytical method utilized in this investigation (ECM), which is to analyze the long and short term, a classical assumption test is also carried out and also a significance test consisting of normality tests, multicholinearity tests, autocorrelation tests, partial tests (t tests), simultaneous tests (F tests), tests using R-Squared and adjusted R-Squared. This study demonstrates that the exchange rate has an impact on Indonesia's trade balance because a stronger exchange rate can positively affect the trade balance by suppressing the value of exports to be higher than the value of imports. Due to unequal global economic growth, anxiety in the global financial markets brought on by the Covid-19 epidemic, impediments in each country's international commerce, and lower-than-anticipated inflation in Indonesia, interest rates and GDP have little impact on Indonesia's trade balance.